Impact of Capital Adequacy Ratio, Net Interest Margin, and Debt to Equity Ratio on the Financial Performance of Nepalese Commercial Banks - Upreti, Roshan (Nepalese Journal of Business, 2024)
This study examines the impact of capital adequacy ratio, net interest margin, and debt-equity ratio on the financial performance of Nepalese commercial banks. Return on assets (ROA) and return on equity (ROE) are the selected dependent variables. The selected independent variables are non-performing loans, capital adequacy ratio, net interest margin, loan-to-deposit ratio, debt to equity ratio, and bank size. The study is based on secondary data of 15 commercial banks with 105 observations for the study period from 2015/16 to 2021/22. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of capital adequacy ratio, net interest margin, and debt-equity ratio on the financial performance of Nepalese commercial banks. The study showed that non-performing loan has a negative impact on return on assets and return on equity. It indicates that increase in non-performing loan leads to decrease in return on assets and return on equity. Similarly, capital adequacy ratio has a negative impact on return on assets and return on equity. It indicates that increase in capital adequacy ratio leads to decrease in return on assets and return on equity. Likewise, net interest margin has a positive impact on return on assets and return on equity. It indicates that increase in net interest margin leads to increase in return on assets and return on equity. In contrast, loan-to deposit ratio has a negative impact on return on assets and return on equity. It indicates that higher the loan-to-deposit ratio, lower would be the return on assets and return on equity. In addition, debt-to-equity ratio has a negative impact on return on assets and return on equity. It indicates that increase in debt-to-equity ratio leads to decrease in return on assets and return on equity. Moreover, bank size has a positive impact on return on assets and return on equity. It indicates that larger the bank size, higher would be the return on assets and return on equity.